Preparation method of primary small particle high-voltage lithium ion battery cathode material
Patent Information
- Application Number
- CN202511438856.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-10
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-10-10
AI Technical Summary
[0004]本发明是要解决锂离子电池正极材料高电压镍锰酸锂的一次颗粒粒径大,电化学性能差的问题,提供了一种一次小颗粒高压锂离子电池正极材料的制备方法,本发明的方法工艺简单,便于大规模生产
[0020] (1) This invention introduces second-phase inert particles LaMnO3 during the preparation of high-voltage lithium nickel manganese oxide cathode materials. Utilizing their pinning effect on grain boundaries, the abnormal growth of primary particles during Ostwald ripening is effectively suppressed. Unlike traditional methods that rely solely on ion doping or surface coating, this invention significantly reduces the particle growth rate through a physical mechanism, resulting in smaller lithium nickel manganese oxide primary particles, approximately 300 nm in size. This not only shortens the diffusion path of lithium ions within the particles and increases the contact area between the material and the electrolyte, improving its kinetic performance, but also alleviates the mechanical stress concentration caused by abrupt volume changes during phase transition, reducing the risk of particle cracking and thus significantly improving cycle stability. Furthermore, it enhances the structural stability of the material, providing a new solution for improving the rate performance and cycle life of high-voltage cathodes.
Smart Images

Figure CN121247900B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrode material synthesis and preparation, specifically to a method for preparing a primary small-particle high-voltage lithium-ion battery cathode material. Background Technology
[0002] With the widespread application of lithium-ion batteries in electric vehicles, energy storage systems, and portable electronic devices, energy density, rate performance, and cycle stability have become key research areas. Lithium nickel manganese oxide (LiNi) 0.5 Mn 1.5 O4 (LNMO) has become one of the most promising cathode materials for high-voltage lithium batteries due to its high voltage, long cycle life, and environmental friendliness. Traditional solid-state lithium nickel manganese oxide (LiNMO) materials typically have large primary particle sizes, approximately 800–1000 nm. This not only results in limited specific surface area and a long lithium-ion diffusion path but also hinders rapid and uniform lithium-ion transport at high rates. During high-rate charge and discharge, concentration polarization easily occurs within large particles, exacerbating the inhomogeneity of the electrochemical reaction, ultimately leading to poor rate performance and reduced capacity retention.
[0003] To address the aforementioned issues, researchers have proposed various modification strategies, including elemental doping, surface coating, nanostructure construction, and the introduction of a second phase. Among these, controlling particle size and crystal growth processes to prevent abnormal particle growth has proven to be an effective way to improve the performance of lithium nickel manganese oxide. Chinese patent CN119517980A, entitled "High-tap-density lithium nickel manganese oxide cathode material, preparation method, and lithium-ion battery," describes a high-tap-density lithium nickel manganese oxide cathode material consisting of micron-sized spherical secondary particles formed by the stacking and aggregation of nanoscale octahedral primary particles. These spherical secondary particles are composed of a mixture of large and small spherical secondary particles, with the average particle size of the large particles ranging from 3 μm. <D 50 <5μm, the average particle size range of small particles is 1. <D 50 <2μm. However, the technical problem of large particle size of lithium nickel manganese oxide particles still exists. Summary of the Invention
[0004] This invention aims to address the problem of large primary particle size and poor electrochemical performance of high-voltage lithium nickel manganese oxide cathode material for lithium-ion batteries. It provides a method for preparing high-voltage lithium-ion battery cathode material with small primary particles. The method of this invention is simple and easy to mass-produce.
[0005] The method for preparing the primary small-particle high-voltage lithium-ion battery cathode material of the present invention is carried out according to the following steps:
[0006] 1. Add the manganese source, nickel source, and inert particle initiator to deionized water in sequence, stir to dissolve, and obtain a clear solution A; add the precipitant to deionized water, stir to dissolve, and obtain a clear solution B.
[0007] 2. Mix solution A and solution B obtained in step one under alkaline and heating conditions to obtain precursor powder C;
[0008] 3. The precursor powder C obtained in step 2 is heated to 600-900℃ at a heating rate of 5-10℃ / min and calcined for 4-7 hours to obtain precursor powder D.
[0009] Fourth, after mixing the precursor powder D obtained in step three with the lithium source, the mixture is heated to 600-900℃ at a heating rate of 5-10℃ / min and calcined for 10-12 hours to obtain a primary small-particle high-voltage lithium-ion battery cathode material.
[0010] Furthermore, the nickel source mentioned in step one is one or a mixture of nickel sulfate, nickel nitrate and nickel chloride.
[0011] Furthermore, the manganese source mentioned in step one is one or a mixture of manganese sulfate, manganese nitrate and manganese chloride.
[0012] Furthermore, the inert particle initiator mentioned in step one is one or a mixture of several of lanthanum sulfate, lanthanum nitrate, and lanthanum chloride.
[0013] Furthermore, the precipitant mentioned in step one is one or a mixture of several of sodium carbonate, sodium bicarbonate, and sodium hydroxide.
[0014] Furthermore, the molar ratio of the nickel source, manganese source, inert particle initiator and precipitant mentioned in step one is 1:(1.5~6):(0.005~0.015):(2~8).
[0015] Furthermore, the ratio of the amount of inert particle source in solution A to the volume of deionized water in step one is (0.0025~0.01) mmol: 1 mL.
[0016] Furthermore, the heating mentioned in step two refers to a temperature of 40~70℃.
[0017] Furthermore, the alkalinity mentioned in step two refers to a pH of 7-8.
[0018] Furthermore, the mass ratio of the precursor powder D to the lithium source in step four is 1:(0.2~0.3).
[0019] The advantages of this invention over the prior art are as follows:
[0020] (1) This invention introduces second-phase inert particles LaMnO3 during the preparation of high-voltage lithium nickel manganese oxide cathode materials. Utilizing their pinning effect on grain boundaries, the abnormal growth of primary particles during Ostwald ripening is effectively suppressed. Unlike traditional methods that rely solely on ion doping or surface coating, this invention significantly reduces the particle growth rate through a physical mechanism, resulting in smaller lithium nickel manganese oxide primary particles, approximately 300 nm in size. This not only shortens the diffusion path of lithium ions within the particles and increases the contact area between the material and the electrolyte, improving its kinetic performance, but also alleviates the mechanical stress concentration caused by abrupt volume changes during phase transition, reducing the risk of particle cracking and thus significantly improving cycle stability. Furthermore, it enhances the structural stability of the material, providing a new solution for improving the rate performance and cycle life of high-voltage cathodes.
[0021] (2) This invention effectively suppresses the two-phase separation of lithium nickel manganese oxide cathode materials during charging and discharging by reducing particle size and regulating structure. Traditional high-voltage lithium nickel manganese oxide materials, during charging and discharging, exhibit phase separation of Li... 0.5 Significant phase separation easily occurs between the Li and Li1 phases, leading to large volume changes and stress accumulation, which affects the cycling performance of the material. By introducing an appropriate amount of inert second-phase particles into the material, the phase transition process was successfully stabilized, phase separation was avoided, and solid solution reactions were promoted. This resulted in a more uniform structure during charge and discharge, significantly improving the cycle stability of the battery.
[0022] (3) The primary small-particle high-voltage lithium-ion battery cathode material of the present invention retains 88.2% of its capacity after 1000 cycles at 25°C and 5C, and has a discharge specific capacity of 95.9 mAh g at a discharge rate of 20C. -1 .
[0023] (4) The raw materials required for the preparation method of the present invention are widely available and have low cost. At the same time, the synthesis process is simple, the product has high reproducibility, and it can be mass-produced at one time to meet the needs of actual applications of lithium-ion batteries. It can be used in the field of lithium-ion batteries. Attached Figure Description
[0024] Figure 1 Scanning electron microscope (SEM) images of the lithium-ion battery cathode materials prepared in Example 1 and Comparative Example 1;
[0025] Figure 2 The X-ray diffraction patterns of the lithium-ion battery cathode materials prepared in Example 1 and Comparative Example 1 are shown below.
[0026] Figure 3 Transmission electron microscope (TEM) images of the lithium-ion battery cathode materials prepared in Example 1 and Comparative Example 1;
[0027] Figure 4 The graph shows the cycling performance of the lithium-ion battery cathode materials prepared in Example 1 and Comparative Example 1 at a 1 C rate.
[0028] Figure 5 The graph shows the cycling performance of the lithium-ion battery cathode materials prepared in Example 1 and Comparative Example 1 at a rate of 5 C.
[0029] Figure 6 The rate performance diagrams are for the lithium-ion battery cathode materials prepared in Example 1 and Comparative Example 1.
[0030] Figure 7 These are scanning electron microscope (SEM) images of the lithium-ion battery cathode materials prepared in Example 2 and Comparative Example 2;
[0031] Figure 8 The graph shows the cycling performance of the lithium-ion battery cathode materials prepared in Example 2 and Comparative Example 2 at a 1 C rate. Detailed Implementation
[0032] The beneficial effects of the present invention will be verified using the following examples.
[0033] Example 1: The preparation method of the primary small-particle high-voltage lithium-ion battery cathode material in this example is carried out according to the following steps:
[0034] 1. Accurately weigh 65.7 g of nickel sulfate hexahydrate, 126.7 g of manganese sulfate monohydrate, and 0.89 g of lanthanum sulfate octahydrate, and add them sequentially to 500 mL of deionized water. Stir to dissolve and obtain a clear solution A.
[0035] Weigh 127.2 g of anhydrous sodium carbonate and add it to 600 mL of deionized water. Stir and dissolve to obtain a clear solution B.
[0036] 2. Weigh 0.6325 g of ammonium bicarbonate and 3.429 mL of ammonia water and dissolve them in 200 mL of deionized water to obtain an alkaline solution. Add the alkaline solution to a four-necked flask and heat the four-necked flask in a water bath at a temperature of 55 °C.
[0037] Solution A and solution B were added to a four-necked flask using a peristaltic pump at a feed rate of 50 mL / h. Co-precipitation was carried out under a stirring rate of 1200 rpm. The pH of the reaction system was 7.5. After the reactants were consumed, the mixture was aged for another 16 h. The precipitate was washed with deionized water and filtered to obtain precursor powder C, i.e., carbonate precursor.
[0038] 3. Place 5 g of precursor powder C obtained in step 2 into a muffle furnace and calcine it at 850 ℃ for 5 h at a heating rate of 5 ℃ / min. After natural cooling, precursor powder D, i.e. oxide precursor, is obtained.
[0039] Fourth, using a pestle, the precursor powder D obtained in step three is uniformly mixed with lithium carbonate powder at a mass ratio of 1:0.2514, and then placed in a muffle furnace and calcined at 800 ℃ for 12 h at a heating rate of 5 ℃ / min. After natural cooling, a primary small-particle high-voltage lithium-ion battery cathode material is obtained.
[0040] Comparative Example 1: This comparative example differs from Example 1 in that lanthanum sulfate octahydrate is not added to solution A in step one. Otherwise, it is the same as Example 1, and lithium nickel manganese oxide, a positive electrode material for lithium-ion batteries, is obtained.
[0041] Figure 1 These are scanning electron microscope (SEM) images of the lithium-ion battery cathode materials prepared in Example 1 and Comparative Example 1. Figure 1 It can be observed that the material of Comparative Example 1 consists of larger primary particles with a particle size of approximately 900 nm, while the material of Example 1 consists of smaller primary particles with a particle size of <300 nm. Smaller primary particles imply shorter Li... + The diffusion pathway and larger electrochemical reaction active surface area result in better rate performance.
[0042] Figure 2 X-ray diffraction patterns of the lithium-ion battery cathode materials prepared in Example 1 and Comparative Example 1. Figure 2 It can be seen that both the samples in Example 1 and Comparative Example 1 can be indexed as lithium nickel manganese oxide (LiNi). 0.5 Mn 1.5 O4 structure. In addition to the main spinel phase, the material of Example 1 exhibited weak impurity phase diffraction peaks at 2θ = 31.2°, 32.4°, and 45.5°, which, upon comparison, correspond to the (200), (121), and (202) crystal planes of LaMnO3 (PDF card number: 89-0682). This indicates that the inert second-phase particles in the material of Example 1 are composed of LaMnO3.
[0043] Figure 3 The image shown is a transmission electron microscope (TEM) image of the lithium-ion battery cathode material prepared in Example 1. From... Figure 3 As can be seen, a La-enriched region exists between the particles in the sample of Example 1. Magnifying this enriched region reveals two regions with different interplanar spacings: one with a spacing of d = 2.04 Å, corresponding to LiNi... 0.5 Mn 1.5The (400) crystal plane of O4, and another crystal plane with a spacing of d = 2.78 Å, belong to the (002) crystal plane of LaMnO3. This also indicates that the composition of the inert second-phase particles is LaMnO3, and the particle size of the inert second-phase particles is about 30 nm, which is one-tenth the particle size of the primary particles of the main phase of lithium nickel manganese oxide. Thus, it is proved that the primary small-particle high-voltage lithium-ion battery cathode material prepared in Example 1 includes a main phase of lithium nickel manganese oxide with a particle size of about 300 nm and a second phase of LaMnO3 with a particle size of about 30 nm.
[0044] Electrodes were prepared using the primary small-particle high-voltage lithium-ion battery cathode material prepared in Example 1 and the lithium-ion battery cathode material lithium nickel manganese oxide prepared in Comparative Example 1. The specific preparation method was as follows: lithium nickel manganese oxide was used as the active material, Super P as the conductive agent, and PVDF as the binder. These were mixed with a paste at a mass ratio of 8:1:1 to obtain a cathode slurry. The slurry was coated onto aluminum foil, dried, and cut into cathode sheets with a diameter of 14 mm. Finally, half-cells were assembled, and the cathodes were tested at 3.5~4.95 V (vs. Li). + Charge and discharge tests were performed within the voltage range of / Li.
[0045] Figure 4 The graph shows the cycling performance of the primary small-particle high-voltage lithium-ion battery cathode material prepared in Example 1 and the lithium-ion battery cathode material lithium nickel manganese oxide prepared in Comparative Example 1 at a 1 C rate. Figure 4 It can be seen that the half-cells assembled using lithium nickel manganese oxide, the positive electrode material of lithium-ion batteries prepared in Example 1 and Comparative Example 1, respectively, exhibit significant differences in performance, ranging from 3.5 to 4.95 V (vs. Li). + Within the voltage range of / Li), at a 1 C rate, the initial discharge specific capacity of the material in Example 1 was 125.4 mAh / g, and after 500 cycles, the discharge specific capacity was 110.1 mAh / g, with a cycle retention rate of 87.7%. In contrast, the lithium nickel manganese oxide cathode material prepared in Comparative Example 1 had an initial discharge specific capacity of 122.9 mAh / g at a 1 C rate, and after 500 cycles at a 1 C rate, the discharge specific capacity was 88.4 mAh / g, with a cycle retention rate of 75.3%. This difference is mainly due to the larger particle size of the primary particles in Comparative Example 1, which significantly affected its volume change during cycling, leading to stress concentration, particle breakage, and a decrease in cycle performance.
[0046] Figure 5The cycling performance of the lithium-ion battery cathode materials prepared in Example 1 and Comparative Example 1 at a 5 C rate was compared. At 5 C rate, Example 1 exhibited an excellent cycle performance with a discharge specific capacity of 110.3 mAh / g after 1000 cycles and a cycle retention rate of 88.2%. In contrast, Comparative Example 1 showed poor cycle performance with an initial discharge specific capacity of 121.1 mAh / g and a discharge specific capacity of 77.1 mAh / g after 1000 cycles, resulting in a cycle retention rate of 63.5%. This is mainly because Comparative Example 1 underwent a two-phase reaction during discharge, which easily generates significant volume changes and interfacial stress. This can lead to electrode cracking during long cycles, affecting electron and lithium-ion transport. Furthermore, the formation of new surfaces causes repeated CEI film formation on the cathode surface, deteriorating the kinetics of lithium insertion / extraction and ultimately resulting in lower capacity retention. In the electrode material of Example 1, the introduction of inert particles successfully reduced the particle size of the primary lithium nickel manganese oxide particles and shortened the Li... + The diffusion path suppresses the two-phase reaction that occurs during discharge. Since the solid solution reaction does not produce a phase interface, the stress is smaller, the particle structure is more stable, the risk of particle breakage is reduced, and the cycle stability is improved.
[0047] Figure 6 The graph shows the rate performance of the primary small-particle high-voltage lithium-ion battery cathode material prepared in Example 1 and the lithium-ion battery cathode material lithium nickel manganese oxide prepared in Comparative Example 1. From... Figure 6 It can be seen that the discharge specific capacities of the primary small-particle high-voltage lithium-ion battery cathode material in Example 1 at 1 C, 10 C, and 20 C rates are 130.3 mAh / g, 111.9 mAh / g, and 95.9 mAh / g, respectively. The discharge specific capacities of the material in Comparative Example 1 at 1 C, 10 C, and 20 C rates are 124.9 mAh / g, 100.4 mAh / g, and 69.5 mAh / g, respectively, all lower than those in Example 1. This indicates that the particle size of the primary particles significantly affects the rate performance of lithium nickel manganese oxide; larger primary particle sizes are detrimental to the electrochemical performance of lithium nickel manganese oxide in lithium-ion batteries.
[0048] Example 2: This example differs from Example 1 in that "0.89 g lanthanum sulfate octahydrate" in solution A in step one is replaced with "1.78 g lanthanum sulfate octahydrate". The other steps and parameters are the same as in Example 1, and lithium nickel manganese oxide, a positive electrode material for lithium-ion batteries, is obtained.
[0049] Comparative Example 2: This comparative example differs from Example 1 in that "0.89 g lanthanum sulfate octahydrate" in solution A in step one is replaced with "3.56 g lanthanum sulfate octahydrate". Other steps and parameters are the same as in Example 1, and lithium nickel manganese oxide, a positive electrode material for lithium-ion batteries, is obtained.
[0050] Figure 7 These are scanning electron microscope (SEM) images of the lithium-ion battery cathode materials prepared in Example 2 and Comparative Example 2. Figure 7 It can be seen that the lithium-ion battery cathode materials prepared in Example 2 and Comparative Example 2 are composed of smaller primary particles with a particle size of <200 nm.
[0051] The lithium-ion battery cathode materials prepared in Example 2 and Comparative Example 2 were used as active materials to assemble batteries using the same method as in Example 1, and the cycle performance of the materials was tested. The cycle performance of the lithium-ion battery cathode materials prepared in Example 2 and Comparative Example 2 at 1C rate is as follows: Figure 8 As shown. From Figure 8 It can be seen that in the range of 3.5~4.95 V (vs. Li) + Within the voltage range of ( / Li), the lithium-ion battery cathode material prepared in Example 2 exhibited an initial discharge specific capacity of 124.4 mAh / g at a 1 C rate, and a discharge specific capacity of 102.1 mAh / g after 500 cycles at a 1 C rate, with a cycle retention rate of 82.1%. The electrochemical performance was slightly lower than that of the material in Example 1, but still better than that of the material in Comparative Example 1.
[0052] The lithium nickel manganese oxide cathode material prepared in Comparative Example 2 exhibited an initial discharge specific capacity of 110.9 mAh / g at 1 C rate. After 500 cycles at 1 C rate, the discharge specific capacity was 79.3 mAh / g, with a cycle retention rate of 78.6%. These performance characteristics are inferior to those of the material in Example 1. This indicates that although the primary particle size of Comparative Example 2 was also significantly reduced, the increased addition of inert particle initiators resulted in an excessive number of LaMnO3 particles in the secondary particles. This severely affected the volume change of the material during cycling, leading to stress concentration, particle breakage, and a decline in cycle performance.
[0053] This invention effectively suppresses the Ostwald ripening process by introducing an appropriate amount of second-phase inert particles during material synthesis, significantly reducing the primary particle size of the high-voltage lithium nickel manganese oxide cathode material and avoiding abnormal particle growth. The resulting material has a larger specific surface area and a shorter lithium-ion diffusion path, thereby improving lithium-ion transport efficiency and enhancing the electrochemical performance at high rates. Simultaneously, the reduced primary particle size improves structural stability, effectively reducing electrode cracking and side reactions during cycling. The high-voltage lithium nickel manganese oxide cathode material prepared by this invention has the advantages of high performance, scalability, and good stability, which helps promote the commercial application of lithium-ion batteries.
Claims
1. A method for preparing a primary small-particle high-voltage lithium-ion battery cathode material, characterized in that, This method is performed in the following steps:
1. Add manganese source, nickel source, and inert particle initiator to deionized water in sequence, stir and dissolve to obtain clear solution A; add precipitant to deionized water, stir and dissolve to obtain clear solution B; wherein the molar ratio of nickel source, manganese source, inert particle initiator to precipitant is 1:(1.5~6):(0.005~0.015):(2~8); wherein the inert particle initiator is one or a mixture of several of lanthanum sulfate, lanthanum nitrate, and lanthanum chloride; 2. Mix solution A and solution B obtained in step one under alkaline and heating conditions to obtain precursor powder C; 3. The precursor powder C obtained in step 2 is heated to 600-900℃ at a heating rate of 5-10℃ / min and calcined for 4-7 hours to obtain precursor powder D. Fourth, after mixing the precursor powder D obtained in step three with the lithium source, the mixture is heated to 600-900℃ at a heating rate of 5-10℃ / min and calcined for 10-12h to obtain a high-voltage lithium-ion battery cathode material composed of primary small particles smaller than 300nm; the high-voltage lithium-ion battery cathode material includes the main phase lithium nickel manganese oxide and the second phase LaMnO3.
2. The method for preparing a primary small-particle high-voltage lithium-ion battery cathode material according to claim 1, characterized in that, The nickel source mentioned in step one is one or a mixture of nickel sulfate, nickel nitrate and nickel chloride.
3. The method for preparing a primary small-particle high-voltage lithium-ion battery cathode material according to claim 1 or 2, characterized in that, The manganese source mentioned in step one is one or a mixture of manganese sulfate, manganese nitrate and manganese chloride.
4. A method for preparing a primary small-particle high-voltage lithium-ion battery cathode material according to claim 1 or 2, characterized in that, The precipitant mentioned in step one is one or a mixture of sodium carbonate, sodium bicarbonate and sodium hydroxide.
5. A method for preparing a primary small-particle high-voltage lithium-ion battery cathode material according to claim 1 or 2, characterized in that, The ratio of the amount of inert particle initiator in solution A to the volume of deionized water in step one is (0.0025~0.01) mmol: 1 mL.
6. A method for preparing a primary small-particle high-voltage lithium-ion battery cathode material according to claim 1 or 2, characterized in that, The heating mentioned in step two refers to heating at a temperature of 40~70℃.
7. A method for preparing a primary small-particle high-voltage lithium-ion battery cathode material according to claim 1 or 2, characterized in that, The alkalinity mentioned in step two refers to a pH of 7-8.
8. A method for preparing a primary small-particle high-voltage lithium-ion battery cathode material according to claim 1 or 2, characterized in that, The mass ratio of precursor powder D to lithium source in step four is 1:(0.2~0.3).
Citation Information
Patent Citations
Lithium nickel manganese oxide positive electrode material with high tap density, preparation method and lithium ion battery
CN119517980A